Transforming agricultural waste into adsorbent: application of Fagopyrum esculentum wheat husks treated with H2SO4 to adsorption of the 2,4-D herbicide (2021)
Wheat husks (Fagopyrum esculentum) were modified by treatment with sulfuric acid. The precursor material (FEWS) and the modified material (TFEWS) were characterized by different techniques to identify the structural changes promoted by the chemical treatment. Subsequently, TFEWS was applied as an adsorbent to remove the 2,4-dichlorophenoxyacetic acid (2,4-D) pesticide from aqueous solutions. Adsorption studies considered the pH effects and adsorbent dosage on the sorption capacity. Also, it evaluated the kinetics, equilibrium, and thermodynamic behavior. Also, the TFEWS was used to treat spiked-pesticide river waters to check its applicability in actual situations. It was found that the pH of the solution had a strong influence on the adsorption process, selecting pH 2 for the subsequent experiments. Regarding the adsorbent dosage, the best relationship between the percentage of herbicide removal (45%) and the material’s adsorption capacity (24 mg g-1) occurred at 0.95 g L-1. The Avrami-fractional order (also known as Bangham) kinetic model better represented the experimental data. In contrast, the Liu model showed the best adjustment of the equilibrium isotherms of the system, reaching a Qmax of 161.1 mg g-1 at 298 K. The thermodynamic behavior pointed to be spontaneous, favorable, and exothermic, consistent with a mechanism involving electrostatic interactions. The material application in situations close to the actual ones presented 76.00% and 76.30% removals for the simulated effluent of the “Conceição” and “Jacuí” rivers, respectively.